Reproductive cicle of the fiddler crab Uca rapax (Smith) (Crustacea, Brachyura, Ocypodidae) at a degraded estuary in Paraty, Rio de Janeiro,Brazil - Castiglioni, Daniela da S.; Negreiros-Fransozo, Maria L. (Soc Brasileira Zoologia, Univ Federal Parana, 2006)
This present work describes the reproductive cycle of Uca rapax (Smith, 1870) based on observations of their gonadal development and molt cycles in a degraded mangrove area in Paraty, State of Rio de Janeiro. Two collectors captured the crabs monthly (from July 2001 to June 2002) during 15 minutes by procedure of capture per unit effort in low tide periods. Crabs were sexed, measured (carapace width -CW; 0.01 mm precision) and females were checked for eggs. Crab' stages of gonad development of both sexes were determined by direct and macroscopic observation and molt stage was estimated by the hardness of the tegument. A total of 1,558 specimens were collected, being 801 males and 757 females (16 ovigerous females). Ovigerous females accounted only about 3% of the population, perhaps because females usually remain underground in closed burrows during the incubation, which can nor be seen easily in the field. Crabs with mature gonads were found year-round, but most reproduction in U. rapax Occurred during the warmer months of the year (spring-summer). The frequency of crabs in molt activity was lower (12.8%) than intermolt crabs. Probably, U. rapax burrowed in this critic period that is the change of exoskeleton, minimizing the risks imposed by the occurrence of a soft skeleton. Despite of U. rapax be occuring in a properly degraded man.-rove, its reproductive cycle seems to be not affected by the habitat condition,when it is compared with areas of the man.-roves no impacted by human action. This fact is Supported by the presence of potentially Mature crabs year-round at the study area.
Keywords: estuary; gonadal development; molt cycle